Historiography and Religious Reform in Brunei during the Period 1912-1959 - Mansurnoor, Iik Arifin (Studia Islamika, 1995)
Scientific papers that discuss the reform of Islam in Southeast Asia has been quite a lot, the literature usually peel reform issues that have a direct relationship with the Islamic central cities, such as Cairo or Istanbul. The most common example is reform inspired by Wahhabism, Tanzimat or Abduhisme are all derived from the center of the region. However, similar works that focus on community studies can be said to be very rare Brunei. This fact is very easy to answer: because Brunei has never experienced such reforms experienced by Muslim communities around it.DOI: 10.15408/sdi.v2i3.828